The impact of board characteristics and ownership structure on earnings management: Evidence from a frontier market - Quynh Lien Le; Huu Anh Nguyen (Cogent Business & Management, 2023)
This paper contributes to the literature by separately examining the impact of board characteristics and ownership structure on upward and downward earnings management of non-financial firms listed on Hanoi Stock Exchange and Ho Chi Minh Stock Exchange. In our research, we conduct Pooled OLS, Fixed and Random effect models, and Generalized least squares. Then, we run a regression with the System Generalized Method of Moments (System GMM) to find the most appropriate model. Firms with high average board age, high ownership concentration, and high financial leverage tend to manage earnings downward. High managerial ownership tends to reduce downward earnings management. Firms with high state ownership reduce upward earnings management. Stakeholders should be more cautious of firms with high average board age, high ownership concentration, high financial performance, and high financial leverage as they tend to manage earnings. Previous studies combined upward and downward earnings management in one regression model, therefore ignoring the chance to investigate the impact of board characteristics and ownership structure on earnings management in each case. The impact of a factor on upward and downward earnings management may be different, and the combination of them in one regression model can drive the findings of previous studies toward errors of unknown directions. Therefore, assessing the effects of board characteristics and ownership structure on earnings management in each case is necessary. To the best of our knowledge, this paper is the first to do so.
Keywords: 650; Board characteristics; earnings management; frontier market; ownership structure